Strategi Peningkatan Produktivitas Kerja Melalui Gaya Kepemimpinan, Kompensasi Dan Motivasi Kerja Pada PT. Mas Sumbiri Semarang - Sri Sulistyaningsih (LPPM STIE Anindyaguna, 2020)
The company's role in reducing poverty and improving the economy of a region and even a country is needed by PT. MAS Sumbiri, which is located at the Wijaya Kusuma Industrial Estate, Semarang, is a manufacturing company engaged in the production of clothing and multinationals. Which in the second semester of 2019 experienced a problem in achieving production targets related to employee performance in the final semester which tended to decline from July until December. The sample in this study were all employees of the production division, totaling 57 employees. The method in this study was a quantitative method with regression analysis using SPSS statistical tools. The results of this study (1). leadership style does not have a positive and significant effect on work productivity. (2). motivation has a positive and significant influence on work productivity, (3). work motivation has a positive and significant influence on work productivity, (4). leadership style, compensation and work motivation, simultaneously affect work productivity and the contribution of the independent variable to the dependent variable based on Adjusted R Square that is equal to 0.621 or 62.1%.